Modification of the Total Reaction Cross-Section Parameterization for the Nucleus-Nucleus Collision with a Correction Factor - Lee, Cheol-Woo; Kim, Jong Kyung (Journal of the Korean Physical Society, 2019)
Enhancement of the parameterization of the total reaction cross- section model for the nucleus-nucleus collision was performed to improve the accuracy of the heavy-ion transport calculation. From the analysis of the experimental data, a linearity between mass difference between target and projectile nucleus and total reaction cross-section is expected. The total reaction cross section model in the Monte Carlo codes was modified with the correction factor to reflect the linearity. The correction factor is estimated with the mass difference between the projectile and target nucleus. As a result, the modified parameterization of the total reaction cross-section was proposed.